Brain Magnetic Resonance Imaging Findings in Developmentally Delayed Children - Ali Akbar Momen; Gholamreza Jelodar; Hamid Dehdashti (International Journal of Pediatrics)
Background. Developmental disorders are failure or inability to acquire various age-specific skills at expected maturational age, which affects about 5–10% of preschool children. One of the most important methods for evaluation of developmentally delayed children is neuroimaging, especially, brain magnetic resonance imaging (MRI) that provides useful information regarding brain tissue structures and anomalies. Method and Material. In this study, hospital records of 580 developmentally delayed children (aged 2 months to 15 years) who admitted in pediatric ward of Golestan Hospital from 1997 to 2009 were selected. Information such as age, MRI findings were collected in the questionnaire and statistically analyzed. Results. Total, 580 children including 333 males (57.4%) and 247 females (42.6%) were studied. Abnormal brain MRI was observed in 340 (58.6%) cases (204 Males, 136 females). The finding includes nonspecific in 38 (6.6%), congenital and developmental anomalies of brain in 39 (6.7%), recognizable syndromes in 3 (0.5%), neurovascular diseases or trauma in 218 (37.6%), and metabolic or neurodegenerative diseases in 42 (7.2%) cases. Conclusion. Because 60% of all study groups showed abnormal brain MRI, using this method could be effective in diagnosis, management, and almost prognosis determination processes.